Gender differences in longevity in early and late reproduced lines of the seed beetle - Stojković Biljana; Savković U. (Archives of Biological Sciences, 2011)
In most animals the average longevity of females is greater than that of males. Among the many explanations of the evolution of sex-specific mortality rates, we tested the hypothesis that sexual selection plays an important role in shaping the longevity and ageing of both sexes. The present study was performed using laboratory populations of Acanthoscelides obtectus, which were obtained either at an early (E) or late (L) age, where the inadvertently created conditions provided opportunities for the evolution of a monogamous and polygamous mating system, respectively. As predicted, under intense sexual selection (L populations) substantial sex differences in longevity were detected both in mated and virgin experimental beetles. On the other hand, monogamy, i.e. relaxation of sexual selection, in E populations resulted in elimination of the differences in longevity between mated females and males, and even led to postponed senescence of virgin males beyond the level exhibited by virgin females.